Reflexiones actuales sobre los cambios de la administración pública - Romero-Pérez, Jorge Enrique (2014)
This article analizes what the neoliberal movement lmpels and crystalizes in the International Financial Organisms (IPO) have called “Stale Reform". That so called start reform deals with changes in the structure and functions of the Public Administration according with the criteria establish by the IFO under the excuse of payment of the external debt. (cf. our book wich was born as a consequence of the Fulbright Scholarship for investigation, Georgetown and American Universitìes, Washington, D. C., USA- The crisis external debt of Latin America, San josé, University mi' Costa Rica, 1.995.).